2005
DOI: 10.4067/s0716-078x2005000300004
|View full text |Cite
|
Sign up to set email alerts
|

Obsessed with grasses?: The case of mara Dolichotis patagonum(Caviidae: Rodentia)

Abstract: The diet of mara (Dolichotis patagonum, Zimmeraman 1780) within the limits of Sierra de las Quijadas National Park (San Luis, Argentina) is described. Other studies regarding mara's diet showed that mara, feeds on different species of grasses and shrubs. However, there is controversy regarding the proportions of these items in the diet or whether this proportion varies seasonally. Considering mara's body size, anatomical features and physiology, we suggest that mara feeds on grasses in a greater proportion tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 7 publications
1
17
0
3
Order By: Relevance
“…The high proportion of succulents ingested in the study period, characterized by an elevated hydric deficit, is similar to that found in other studies with brocket deer in extreme dry areas like the boreal Chaco of Paraguay (Stalling, 1984) and the plains of La Rioja (Cartes Yegros, 1999), during the same season. The selection of succulent plants and cacti detected in this study is possibly related to the deer's water requirements (Stalling, 1984;Sombra and Mangione, 2005), which seems consistent, as the study was conducted during the dry season when water was limited. Our results suggest that leaves of woody plants, cacti and the fruits of both are important sources of food and water for the grey brocket deer in Chancaní Reserve, which allows them to survive in arid areas during a period of scarce resources.…”
Section: Discussionsupporting
confidence: 69%
“…The high proportion of succulents ingested in the study period, characterized by an elevated hydric deficit, is similar to that found in other studies with brocket deer in extreme dry areas like the boreal Chaco of Paraguay (Stalling, 1984) and the plains of La Rioja (Cartes Yegros, 1999), during the same season. The selection of succulent plants and cacti detected in this study is possibly related to the deer's water requirements (Stalling, 1984;Sombra and Mangione, 2005), which seems consistent, as the study was conducted during the dry season when water was limited. Our results suggest that leaves of woody plants, cacti and the fruits of both are important sources of food and water for the grey brocket deer in Chancaní Reserve, which allows them to survive in arid areas during a period of scarce resources.…”
Section: Discussionsupporting
confidence: 69%
“…The ''grazer'' type attributed to the mara in the present study is justified by the high dietary proportion of grasses on both sampling sites, as can be observed in some other mara populations (Campos et al, 2001b;Sombra and Mangione, 2005). Nevertheless, it is important to recognize the relevance of low and tall shrubs as alternative food items for the mara during autumn-winter, when grasses become senescent.…”
Section: Discussionmentioning
confidence: 83%
“…Avoidance of a major grass in the vegetation, Panicum, and preference for scarce species such as the grass Bromus, the tall shrub Lycium and the low shrub Prosopis, are responsible for the higher Kufner et al, 1992;Campos et al, 2001b), Monte-Chaco ecotone (MC E, Sombra and Mangione, 2005), Monte-Espinal ecotone (ME E, Rodriguez and Dacar, 2008), and Southern arid Chaco (S CH, Chillo, 2007). Locations are ordered according to increasing rainfall and temperature.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations